Back to the Source: Consumers Response to Produce Irrigated With Different Sources of Recycled Water - Sean F. Ellis; Diya Ganguly; Maik Kecinski; Kent D. Messer (Water Resources Research, 2023)
Abstract Using recycled water to irrigate agricultural products can be an effective solution to water scarcity and security. However, a better understanding of how society values different sources of recycled water provides insights into potential demand‐side barriers to adoption of these solutions. This paper implements a framed field experiment conducted in the Southwest and Mid‐Atlantic regions of the United States that evaluates consumers' willingness‐to‐pay (WTP) for three sources of recycled irrigation water: “gray,” “black,” and “produced.” Our analysis indicates that people consider certain sources of recycled water more acceptable for irrigating produce than others. Recycled gray water is preferred to recycled produced water, and both are preferred to recycled black water. We also explore how people respond to scientific information about the benefits and risks of using recycled irrigation water and found no evidence to support that this information changes people's behaviors.